Strategi Pedagogis Adaptif dalam Menyelaraskan Gaya Mengajar dengan Budaya Media Digital Generasi Z - Husnaini Nuradila; Yuliana Nurul Fatimah; Aulia Shandika Abidin; M. Fasha Al Fikri; Nurul Mahfuza (Indonesian Journal of Action Research, 2026)
Purpose – This study aims to examine adaptive pedagogical strategies in aligning teaching styles with the digital media culture of Generation Z. The rapid development of digital technology has significantly transformed students’ learning behavior, communication patterns, and social interactions. Conventional teaching approaches are often considered less relevant to the characteristics of Generation Z, who are closely connected to digital media and interactive learning environments. Therefore, this study seeks to explore how adaptive pedagogical approaches can create more contextual, engaging, and meaningful learning experiences for Generation Z learners. Design/methods– This study employed a qualitative descriptive approach through library research. Data were collected from various academic sources, including books, journal articles, research reports, and relevant scientific publications discussing adaptive pedagogy, digital media culture, and Generation Z learning characteristics. The data were analyzed using content analysis techniques to identify patterns, concepts, and pedagogical strategies relevant to contemporary educational contexts Findings – The findings indicate that adaptive pedagogical strategies are essential in responding to the learning culture of Generation Z. Digital media has shaped students’ preferences toward interactive, visual, collaborative, and technology-based learning experiences. Consequently, educators are required to transform conventional teaching practices into more flexible and student-centered approaches. The study also found that the integration of digital media, interactive learning methods, and contextual communication can enhance student engagement and participation in learning processes.